Association between nutritional level, menstrual-related symptoms, and mental health in female medical students. - Keiko Fukushima; Noritoshi Fukushima; Hiroki Sato; Jinko Yokota; Keiko Uchida (PLoS ONE)
Objective Research suggests that medical students as well as women are at greater risk of depression compared to the general population and men. This suggests that female medical students are crucial targets requiring specific monitoring for mental health disorder prevention and intervention. However, little is known regarding the risk factors for poor mental health among this population. Therefore, we investigated whether menstrual symptoms and nutritional status are associated with psychological distress in Japanese female medical students. Methods This cross-sectional study assessed 326 female medical students who attended a school medical check-up, which included blood sampling in 2018. The levels of psychological distress were evaluated using the Japanese General Health Questionnaire (J-GHQ)-30. We defined high GHQ scores as GHQ-30 ≥7. We checked dysmenorrhea levels and assessed menstrual symptoms according to the presence of premenstrual syndrome (PMS). Dysmenorrhea was evaluated according to quartiles of the sum of the Menstrual Distress Questionnaire (MDQ). PMS was assessed using the Premenstrual Symptoms Questionnaire (PSQ). We evaluated levels of serum albumin, hemoglobin, ferritin, and lipid metabolite as nutritional factors. A multivariate logistic regression analysis was used to identify the association between menstrual-related symptoms or nutritional factors and the levels of psychological distress. Results A total of 45 female medical students (15%) experienced psychological distress. Serum albumin levels were associated with psychological distress, while lipid metabolite levels were not. The intensity of dysmenorrhea and the presence of PMS were associated with psychological distress, independent of nutritional status. Conclusion Both menstrual symptoms and nutrition markers were associated with the levels of psychological distress in Japanese female medical students. School doctors and nurses can help improve the mental health of young female medical students by encouraging a healthy diet and checking for the presence of menstrual symptoms.